2022
DOI: 10.3390/ijerph20010031
|View full text |Cite
|
Sign up to set email alerts
|

Building Trust and Awareness to Increase AZ Native Nation Participation in COVID-19 Vaccines

Abstract: The goal of this study was to establish effective, culturally appropriate strategies to enhance participation of American Indian/Alaska Native (AI/AN) communities in prevention and treatment of COVID-19, including vaccine uptake. Thirteen Community Health Representatives (CHRs) from three Arizona Native nations tailored education materials to each community. CHRs delivered the intervention to over 160 community members and administered a pre-posttest to assess trusted sources of information, knowledge, and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In September 2021, SHERC received an administrative supplement aimed at building trust and awareness to increase Arizona Native Nation participation in COVID-19 vaccine trials and vaccines. Methodological details and results related to the broader study results are reported in this special issue [13]. Together, researchers leveraged expertise and community partnerships to engage in culturally centered community-based research to strengthen vaccine and clinical trial awareness among American Indian communities of Arizona disproportionately impacted by COVID-19.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In September 2021, SHERC received an administrative supplement aimed at building trust and awareness to increase Arizona Native Nation participation in COVID-19 vaccine trials and vaccines. Methodological details and results related to the broader study results are reported in this special issue [13]. Together, researchers leveraged expertise and community partnerships to engage in culturally centered community-based research to strengthen vaccine and clinical trial awareness among American Indian communities of Arizona disproportionately impacted by COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…A total of three educational materials were created for each community: (1) COVID-19 Vaccine Information, (2) COVID-19 FAQs and Myths, and (3) COVID-19 Clinical Trials. Materials are available as supplemental files in Sears et al [13]. Materials were provided to participants by a CHR through regularly scheduled home visits and community events.…”
Section: Step 2: Chr Brief Education Development and Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Building trust 24 Family physicians are often highly respected members of the community in rural areas. They can use their existing relationships and credibility to build trust with patients who are hesitant about vaccines.…”
Section: Measure Explanationmentioning
confidence: 99%